Retrospective analysis of necrotizing typhlitis cases associated with Brachyspira spp. in British rheas. Issue 3 (4th May 2021) - McFadzean, Harriet; Schock, Alex; Stubberfield, Emma; Card, Roderick M.; Thomson, Jill; Rohde, Judith; Murray, Laura; Velo-Rego, Elena; Ainsworth, Heather; Barlow, Alex M.; Welchman, David
ABSTRACT: This paper describes a retrospective analysis of necrotizing typhlitis in common rheas ( Rhea americana ) diagnosed in the United Kingdom by the Animal & Plant Health Agency (APHA). From January 2008 to January 2020, seven cases of spirochaetal typhlitis associated with Brachyspira spp. were identified using the Veterinary Investigation Diagnosis Analysis database. Gross examination was combined with selective anaerobic culture, polymerase chain reaction, and histopathology to diagnose typhlitis associated with spirochaetal infection. Whole-genome sequencing was subsequently utilized on archived isolates from six of the seven submissions, overcoming issues with traditional testing methods and yielded gains in the identification of Brachyspira to species level. Brachyspira hyodysenteriae, an organism traditionally associated with typhlitis in rheas, was isolated in three sequenced submissions. One of these also demonstrated co-infection with Brachyspira intermedia . Brachyspira suanatina, Brachyspira hampsonii, and Brachyspira alvinipulli were identified by sequencing as single infections in the remaining three animals. This report demonstrates the ability of Brachyspira species other than B. hyodysenteriae to colonize the caeca of rheas presenting with typhlitis. Additionally, the B. alvinipulli isolate harboured a tva (A) gene, indicating higher potential pleuromutilin resistance, which has not previously been described in this Brachyspira species. This study discusses the epidemiology of examined cases and examines the potential role other species may play in these outbreaks.